Hypertension evaluated in the public and private Brazilian health system hypertension in public and private service - Amorim, Kecia C. F. O.; Vitorino, Priscila Valverde O.; Feitosa, Audes D. M.; Santos, Mayara Cedrim; Bezerra, Rodrigo; Lopes, Lais Rocha; Camafort, Miguel; Coca, Antonio; Sousa, Ana Luíza Lima; Barroso, Weimar K. S. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Hypertension (HT) remains the leading cause of death worldwide. In Brazil it is estimated that 35% of the adult population has HT and that about 20% of these have blood pressure values within the targets recommended for the reduction of cardiovascular risk. There are some data that point to different control rates in patients treated by cardiologists in public and private referral center and this is an important point to be investigated and discussed. Objective To compare sociodemographic characteristics, body mass index (BMI), antihypertensive (AH) drugs, blood pressure (BP) and control rate in public (PURC) and private (PRRC) referral centers. Methodology A cross-sectional multicenter study that analyzed data from hypertensive patients assisted by the PURC (one in Midwest Region and other in Northeast region) and PRRC (same distribution). Variables analyzed: sex, age, BMI, classes, number of AH used and mean values of systolic and diastolic BP by office measurement and home blood pressure measurement (HBPM). Uncontrolled hypertension (HT) phenotypes and BP control rates were assessed. Descriptive statistics and χ2 tests or unpaired t-tests were performed. A significance level of p < 0.05 was considered. Results A predominantly female (58.9%) sample of 2.956 patients and a higher prevalence of obesity in PURC (p < 0.001) and overweight in PRRC (p < 0.001). The mean AH used was 2.9 ± 1.5 for PURC and 1.4 ± 0.7 for PRRC (p < 0.001). Mean systolic and diastolic BP values were higher in PURC as were rates of uncontrolled HT of 67.8% and 47.6% (p < 0.001) by office measurement and 60.4% and 35.3% (p < 0.001) by HBPM in PURC and PRRC, respectively. Conclusion Patients with HT had a higher prevalence of obesity in the PURC and used almost twice as many AH drugs. BP control rates are worse in the PURC, on average 15.3 mmHg and 12.1 mmHg higher than in the PRRC by office measurement.